Two-dimensional numerical study of two-phase rotating detonation wave with different injections - Bo Sun; Hu Ma (AIP Advances, 2019)
Two-dimensional numerical simulations on the two-phase rotating detonation wave of a stoichiometric ratio of the air-octane mixture by the discrete phase model are performed. The propagation process and stable flow field of the rotating detonation wave under nonpremixed and nonuniform injection conditions are analyzed. The effects of air injection total temperature and fuel injection inhomogeneity on the gas-liquid two-phase rotating detonation wave are investigated. The results show that under the same conditions, with the increase in the total temperature of air injection, the peak temperature, height, and propagation velocity of the detonation wave increase, but the peak pressure of the detonation wave decreases. The larger the jet spacing, the more pronounced the detonation wave is disturbed by the fuel jet. As the fuel jet spacing increases, the detonation wave propagation velocity decreases, but the peak temperature and peak pressure of the detonation wave increase. For the case of a jet spacing of 10 mm, the detonation wave cannot propagate when the air total temperature is 300 K, but the detonation wave can be stably propagated when the air total temperature is increased to 600 K. The stable propagation boundary of the rotating detonation wave with the combined action of the air total temperature and the jet spacing is obtained.